Adipose Stem Cell-Based Clinical Strategy for Neural Regeneration: A Review of Current Opinion - Yu-hao Wang; Yu-chen Guo; Dian-ri Wang; Ji-yuan Liu; Jian Pan (Hindawi Limited, 2019)
Nerve injury is a critical problem in the clinic. Nerve injury causes serious clinic issues including pain and dysfunctions for patients. The disconnection between damaged neural fibers and muscles will result in muscle atrophy in a few weeks if no treatment is applied. Moreover, scientists have discovered that nerve injury can affect the osteogenic differentiation of skeletal stem cells (SSCs) and the fracture repairing. In plastic surgery, muscle atrophy and bone fracture after nerve injury have plagued clinicians for many years. How to promote neural regeneration is the core issue of research in the recent years. Without obvious effects of traditional neurosurgical treatments, research on stem cells in the past 10 years has provided a new therapeutic strategy for us to address this problem. Adipose stem cells (ASCs) are a kind of mesenchymal stem cells that have differentiation potential in adipose tissue. In the recent years, ASCs have become the focus of regenerative medicine. They play a pivotal role in tissue regeneration engineering. As a type of stem cell, ASCs are becoming popular for neuroregenerative medicine due to their advantages and characteristics. In the various diseases of the nervous system, ASCs are gradually applied to treat the related diseases. This review article focuses on the mechanism and clinical application of ASCs in nerve regeneration as well as the related research on ASCs over the past decades.